Disruption of protein kinase A localization induces acrosomal exocytosis in capacitated mouse sperm - Stival, Cintia Estefanía (2018)
Protein kinase A (PKA) is a broad-spectrum Ser/Thr kinase involved in the regulation of several cellular activities. Thus, its precise activation relies on being localized at specific subcellular places known as discrete PKA signalosomes. A-Kinase anchoring proteins (AKAPs) form scaffolding assemblies that play a pivotal role in PKA regulation by restricting its activity to specific microdomains. Because one of the first signaling events observed during mammalian sperm capacitation is PKA activation, understanding how PKA activity is restricted in space and time is crucial to decipher the critical steps of sperm capacitation. Here, we demonstrate that the anchoring of PKA to AKAP is not only necessary but also actively regulated during sperm capacitation. However, we find that once capacitated, the release of PKA from AKAP promotes a sudden Ca2+ influx through the sperm-specific Ca2+ channel CatSper, starting a tail-to-head Ca2+ propagation that triggers the acrosome reaction. Three-dimensional super-resolution imaging confirmed a redistribution of PKA within the flagellar structure throughout the capacitation process, which depends on anchoring to AKAP. These results represent a new signaling event that involves CatSper Ca2+ channels in the acrosome reaction, sensitive to PKA stimulation upon release from AKAP.